Sub-acute stroke demonstrates altered beta oscillation and connectivity pattern in working memory - Mao, Lin; Che, Xianwei; Wang, Juehan; Jiang, Xiaorui; Zhao, Yifan; Zou, Liliang; Wei, Shuang; Pan, Shuyi; Guo, Dazhi; Zhu, Xueqiong; Hu, Dongxia; Yang, Xiaofeng; et al. (Journal of neuroengineering and rehabilitation, 2024)
Working memory (WM) is suggested to play a pivotal role in relearning and neural restoration during stroke rehabilitation. Using EEG, this study investigated the oscillatory mechanisms of WM in subacute stroke. This study included 48 first subacute stroke patients (26 good-recovery, 22 poor-recovery, based on prognosis after a 4-week period) and 24 matched health controls. We examined the oscillatory characteristics and functional connectivity of the 0-back WM paradigm and assessed their associations with prognosis. Patients of poor recovery are characterised by a loss of significant beta rebound, beta-band connectivity, as well as impaired working memory speed and performances. Meanwhile, patients with good recovery have preserved these capacities to some extent. Our data further identified beta rebound to be closely associated with working memory speed and performances. We provided novel findings that beta rebound and network connectivity as mechanistic evidence of impaired working memory in subacute stroke. These oscillatory features could potentially serve as a biomarker for brain stimulation technologies in stroke recovery.